Elevated Levels of Procalcitonin and Interleukin-6 are Linked with Postoperative Complications in Cardiac Surgery - Brocca, A; Virzì, G M; de Cal, M; Giavarina, D; Carta, M; Ronco, C (Scandinavian journal of surgery : SJS : official organ for the Finnish Surgical Society and the Scandinavian Surgical Society, 2017)
Cardiac surgery-associated acute kidney injury is a frequent and serious postoperative complication of cardiac surgery and is associated with an increased risk of morbidity, mortality, and length stay. In this study, we hypothesized that persistent elevation in inflammation in the first 48 h might be a powerful predictor of clinical outcome. Our aim was to elucidate the usefulness of interleukin-6 and procalcitonin postoperative levels in predicting mortality and renal complications in cardiac surgery patients. A total of 122 cardiac surgery patients were enrolled. Procalcitonin and interleukin-6 concentrations were measured on the second postoperative day, and their levels were evaluated versus a number of conditions and endpoints. Procalcitonin has a good predictive value for adverse renal outcome (p < 0.05). Interleukin-6 has a good predictive value for 30 days and overall mortality in cardiac surgery population (p < 0.05). We did not observe a significant difference in procalcitonin and interleukin-6 levels among patients with different types of surgery and different extracorporeal circulation time, but the levels of both the molecules increase significantly depending on number of transfusions received by patients (p < 0.01). We speculated that procalcitonin and interleukin-6 could be two effective biomarkers. There is a possibility of having a combined inflammatory multi-biomarker panel, with procalcitonin for predicting renal outcome and interleukin-6 for predicting mortality.